How do you simplify 3sqrt32 - 6sqrt833268?

2 Answers
May 15, 2015

3sqrt32 - 6sqrt8 33268

the expression can be written as :
3sqrt(4xx8) - 6sqrt834×868

(we know that sqrt(4) = 24=2)

=3 xx 2sqrt(8) - 6sqrt8=3×2868

6sqrt(8) - 6sqrt8 = 06868=0

May 15, 2015

Simplify 3sqrt32-6sqrt833268 .

Simplify 3sqrt32332.

3sqrt(4*4*2)3442 =

3sqrt4sqrt4sqrt23442 =

3*2*2sqrt23222 =

3*4sqrt2342 =

12sqrt2122

Simplify 6sqrt868.

6sqrt868 =

6sqrt2*2*26222 =

6sqrt(4*2)642 =

6*2sqrt2622 =

12sqrt2122

Rewrite equation with simplified terms.

12sqrt2-12sqrt2=0122122=0